The feasibility, acceptability, cost and benefits of a “communities of practice” model for improving the quality of childcare centres: a mixed-methods study in the informal settlements in Nairobi - Nampijja, Margaret; Langat, Nelson; Oloo, Linda; Amboka, Patrick; Okelo, Kenneth; Muendo, Ruth; Habib, Sabrina; Kiyeng, Martin; Ray, Anna; Abboah-Offei, Mary; Kitsao-Wekulo, Patricia; Kimani-Murage, Elizabeth; et al. (Frontiers in Public Health, 2023)
Background: Informal childcare centres have mushroomed in the informal settlements of Nairobi, Kenya to meet the increasing demand. However, centre providers are untrained and the facilities are sub-standard, threatening children's health and development. We aimed to co-design and test the feasibility, acceptability, cost and potential benefits of a communities of practice (CoP) model where trained community health volunteers (CHVs) provide group training sessions to improve center providers' improve skills and practices. Methods: A CoP model was co-designed with sub-county health teams, centre providers and parents with inputs from Kidogo, government nutritionists and ECD experts and implemented in 68 childcare centres by trained CHVs. Its feasibility and potential benefits were measured quantitatively and qualitatively. Centre provider (n=68) and CHV (n=20) knowledge and practice scores before and after the intervention were assessed and compared. Intervention benefits were examined using linear regressions adjusting for potential confounding factors. We conducted in-depth interviews with 10 parents, 10 CHVs, 10 centre providers and 20 government officials, and two focus groups with CHVs and centre providers. Qualitative data were analysed, focusing on feasibility, acceptability, potential benefits, challenges and ideas for improvement. Cost for delivering and accessing the intervention were examined. Results: The intervention was acceptable and feasible to deliver within existing government community health systems; 16 CHVs successfully facilitated CoP sessions to 58 centre providers grouped into 13 groups each with 5-6 centre providers, each group receiving 4 sessions representing the four modules. There were significant improvements in provider knowledge and practice (effect size=0.40; p<0.05) and quality of centre environment (effect size=0.56; p<0.01) following the intervention. CHVs’ scores showed no significant changes due to pre-existing high knowledge levels. Qualitative interviews also reported improvements in knowledge and practices and the desire for continued intervention.. The total explicit costs were USD 22,598 and the total opportunity costs were USD 3,632 (IQR; USD 3,570, USD 4,049). Conclusion: A simple model delivered by CHVs was feasible and has potential to improve the quality of informal childcare centres. Leveraging these teams and integration of the intervention into the health system is likely to enable scale-up and sustainability in Kenya and similar contexts.